Analisis Pendapatan Pedagang Kaki Lima Selama Masa Pandemi Covid-19 di Alun-Alun Kota Blitar - Ernawati, Lili; Kusuma , Hendra (Program Studi Ekonomi Pembangunan, 2022)
The study was aimed at getting a description of the five-foot hawker (PKL) during the covid-19 pandemic at the city Blitar, and to find out how much the street vendor (PKL) had gained during the covid-19 pandemic in the city’s Blitar square. The study includes qualitative research, and it uses income analysis, cost analysis, and profit analysis. The population in the study is about 30 traders. According to the research, the characteristics of the five-foot traders in the city square at Blitar in the face of such pandemics continue to carry out the government’s imposes health protocols, with competition incrasingly intense as people or costumer do not have a lotof outdoor activities, and in the light of income, while income is declining because of a lack of difinite income, and most of the people don’t do anything outside the house.